Native Indonesian Herbs: Challenges in The Future for Anti-Cancer Drugs - Dias Rima Sutiono; Malvel Mario Gabriel Reinald Salim; Nadya -; Oniko Liani; Sulvania Susanto (Cermin Dunia Kedokteran, 2020)
Indonesia has undoubtedly enormous biodiversitywith great potential for drug discovery; however, its utilization is still very limited. Current available cancer treatments are still not really effective since they are rather invasive, has side effects, expensive, and not really specific. Researches start to focus on the natural-based anticancer drugs and lots of native Indonesian herbs have been scientifically identified to have anticancer properties. White turmeric, clove, ant plant, and rodent tuber plant are some of native Indonesian herbs that have been proven to have anticancer properties. This review is to demonstrate the anticancer properties of these potential native Indonesian herbs to be the future natural anticancer drugs and also to inspire the utilization of rich Indonesian biodiversity.Indonesia memiliki keanekaragaman hayati yang sangat melimpah dan berpotensi sangat besar untuk penemuan obat baru, namun pemanfaatannya masih sangat terbatas. Pengobatan kanker saat ini tidak terlalu efektif karena bersifat invasif, memiliki efek samping, mahal, dantidak terlalu spesifik. Penelitian mulai berfokus kepada obat anti-kanker alami sehingga pemanfaatan keanekaragaman hayati Indonesia menjadi sangat sesuai karena banyaknya tanaman herbal asli Indonesia yang telah teridentifikasi secara ilmiah memiliki kandungan anti-kanker. Kunyit putih, cengkeh, sarang semut, dan keladi tikus adalah beberapa tumbuhan herbal asli Indonesia yang telah terbukti memiliki kandungan anti-kanker. Tinjauan pustaka ini bertujuan untuk mendemonstrasikan potensi kandungan anti-kanker tumbuh-tumbuhan tersebut di masa depan dan juga untuk menginspirasi pemanfaatan keanekaragaman hayati Indonesia.